Methodological instructions for the performance of individual calculation tasks in the discipline "Relationship marketing" - Raiko, Diana (Національний технічний університет "Харківський політехнічний інститут", 2024)
Methodical guidelines for the implementation of individual calculation tasks in the discipline "Relationship Marketing". Educational and methodical support includes methodical advice for the implementation of an individual calculation task in the discipline: necessary explanations for the task; practical tasks for the development and approval of methodological provisions for modeling the budget of information interaction between enterprises, partners, consumers as part of the "consumer - enterprise - partner" system, which is the core of information interaction on the example of an enterprise - a practice base. Intended for applicants of specialty 075 "Marketing" of all forms of education.
Keywords: methodological instructions; individual calculation tasks; marketing of relations; marketing; relationship marketing; consumers